Continuous clinical remission with biologics in ulcerative colitis: the 'AURORA' comparison study. Issue 12 (23rd September 2022) - Cassinotti, Andrea; Mezzina, Nicolò; De Silvestri, Annalisa; Di Paolo, Dhanai; Lenti, Marco Vincenzo; Bezzio, Cristina; Stradella, Davide; Mauri, Martina; Zadro, Valentina; Ricci, Chiara; Casini, Valentina; Radice, Elisa; et al.
Abstract : Objectives: Comparative trials among biological drugs for the treatment of ulcerative colitis (UC) provided conflicting results. After patent expire of infliximab originator, adalimumab, infliximab biosimilar, golimumab and vedolizumab have been approved in Italy. We compared the efficacy of these four biologics in UC according to the concept of continuous clinical remission (CCR). Methods: In a retrospective, multicentre study, all UC patients treated with adalimumab, infliximab biosimilar, golimumab or vedolizumab between 2014 and 2019 were included. All drugs were compared to each other according to the 1-year CCR rate, defined as Mayo partial score ≤2, with bleeding subscore = 0, without any relapse or optimization with dose escalation, topical treatments or steroid use after first clinical remission. Results: Four-hundred sixteen patients (adalimumab = 90, infliximab biosimilar = 105, golimumab = 79, vedolizumab = 142) were included. CCR was achieved in similar percentages among the groups (33%, 37%, 28%, 37%, respectively). All drugs were equivalent in biologic-naive patients, while vedolizumab was better than a second anti-TNFα in prior anti-TNFα agent failures. No differences were found according to type of adverse events or severe adverse events. Conclusions: Based on a strict definition of clinical remission, all biologics appear equally effective at 1 year. Changing to vedolizumab is more effective than switching to another anti-TNFα in TNFα failures.